1. Rewrite the expression in terms of logarithms:
![y=x^x=e^(\ln x^x)=e^(x\ln x)](https://img.qammunity.org/2021/formulas/mathematics/college/tpm8b34omxzd3qh7xkih6iqmdekqjpfq0p.png)
Then differentiate with the chain rule (I'll use prime notation to save space; that is, the derivative of y is denoted y' )
![y'=e^(x\ln x)(x\ln x)'=x^x(x\ln x)'](https://img.qammunity.org/2021/formulas/mathematics/college/ong2td02yszxv6jdi016fkxygbidxovu17.png)
![y'=x^x(x'\ln x+x(\ln x)')](https://img.qammunity.org/2021/formulas/mathematics/college/7yvc8l5sbgf2k23lwnj9w7wjc93blvlw4v.png)
![y'=x^x\left(\ln x+\frac xx\right)](https://img.qammunity.org/2021/formulas/mathematics/college/g2h5zix2mtjqqog99xpmtcnw574t3i8qb7.png)
![y'=x^x(\ln x+1)](https://img.qammunity.org/2021/formulas/mathematics/college/fuc8suz5vpr5r5605jar8g0lyqs5aehpqi.png)
2. Chain rule:
![y=\ln(\csc(3x))](https://img.qammunity.org/2021/formulas/mathematics/college/75wbvhqe45kae30voqsdopiutgllkugmog.png)
![y'=\frac1{\csc(3x)}(\csc(3x))'](https://img.qammunity.org/2021/formulas/mathematics/college/dep58cfc8pigj4iachedzkxpyzl5wa7hdd.png)
![y'=\sin(3x)\left(-\cot^2(3x)(3x)'\right)](https://img.qammunity.org/2021/formulas/mathematics/college/rz4942k7htqehes1j8eeljt229r8ah8xdw.png)
![y'=-3\sin(3x)\cot^2(3x)](https://img.qammunity.org/2021/formulas/mathematics/college/5y7v4grrwlk79m2lm1y878t01trs74pdvg.png)
Since
, we can cancel one factor of sine:
![y'=-3(\cos^2(3x))/(\sin(3x))=-3\cos(3x)\cot(3x)](https://img.qammunity.org/2021/formulas/mathematics/college/hoec94qrkf3i2w2ldxeffq2famcwje8a6i.png)
3. Chain rule:
![y=e^{e^(\sin x)}](https://img.qammunity.org/2021/formulas/mathematics/college/wm89orzubo47ma4rby81egi3vunipanv3p.png)
![y'=e^{e^(\sin x)}\left(e^(\sin x)\right)'](https://img.qammunity.org/2021/formulas/mathematics/college/rxiobqjmnamw50u6owb31bm6spjrcznlq7.png)
![y'=e^{e^(\sin x)}e^(\sin x)(\sin x)'](https://img.qammunity.org/2021/formulas/mathematics/college/4m3oglpkq9d06ciykojgk5mpxj7vri3noq.png)
![y'=e^{e^(\sin x)+\sin x}\cos x](https://img.qammunity.org/2021/formulas/mathematics/college/pmtm4jckbjv6mf7mvuownbxxnh3z8lk7vx.png)
4. If you're like me and don't remember the rule for differentiating logarithms of bases not equal to e, you can use the change-of-base formula first:
![\log_2x=(\ln x)/(\ln2)](https://img.qammunity.org/2021/formulas/mathematics/college/aehtkszq6hc6cbxbtd7i8tunmqu1a29dii.png)
Then
![(\log_2x)'=\left((\ln x)/(\ln 2)\right)'=\frac1{\ln 2}](https://img.qammunity.org/2021/formulas/mathematics/college/b8783djgboh8n2w7bd7ih6yu2gmlh438ym.png)
So we have
![y=\cos^2(\log_2x)](https://img.qammunity.org/2021/formulas/mathematics/college/nppw1jh47p4nps46wxrk4l55kyjlgjh69n.png)
![y'=2\cos(\log_2x)\left(\cos(\log_2x)\right)'](https://img.qammunity.org/2021/formulas/mathematics/college/pm3d40aac3zba98gifgitw9c9u8bwytzhq.png)
![y'=2\cos(\log_2x)(-\sin(\log_2x))(\log_2x)'](https://img.qammunity.org/2021/formulas/mathematics/college/lwsksdnpgsj7ly75wh7021m4q61gz3ycyc.png)
![y'=-\frac2{\ln2}\cos(\log_2x)\sin(\log_2x)](https://img.qammunity.org/2021/formulas/mathematics/college/i3xg0btvblawpytkhdj7p4hde33vmh18ih.png)
and we can use the double angle identity and logarithm properties to condense this result:
![y'=-\frac1{\ln2}\sin(2\log_2x)=-\frac1{\ln2}\sin(\log_2x^2)](https://img.qammunity.org/2021/formulas/mathematics/college/42k2n2ub88o4y6h1h5oxq5jf4tlyz8e81n.png)
5. Differentiate both sides:
![\left(x^2-y^2+\sin x\,e^y+\ln y\,x\right)'=0'](https://img.qammunity.org/2021/formulas/mathematics/college/weklbbxb9nlu6kw3r4t9pcrvjlnc46dsxc.png)
![2x-2yy'+\cos x\,e^y+\sin x\,e^yy'+\frac{xy'}y+\ln y=0](https://img.qammunity.org/2021/formulas/mathematics/college/2imns94jgju5xb8g1e1ohjr16wu1b247nj.png)
![-\left(2y-\sin x\,e^y-\frac xy\right)y'=-\left(2x+\cos x\,e^y+\ln y\right)](https://img.qammunity.org/2021/formulas/mathematics/college/kkteiooe8dy8g0h1ejer2s5g922w6nqaqf.png)
![y'=(2x+\cos x\,e^y\ln y)/(2y-\sin x\,e^y-\frac xy)](https://img.qammunity.org/2021/formulas/mathematics/college/pufruu0omzw7f0l3b3udor76yztup2jqy3.png)
![y'=(2xy+\cos x\,ye^y\ln y)/(2y^2-\sin x\,ye^y-x)](https://img.qammunity.org/2021/formulas/mathematics/college/9f3ka1n250x39lsh54bxvwrvx9xv96m420.png)
6. Same as with (5):
![\left(\sin(x^2+\tan y)+e^(x^3\sec y)+2x-y+2\right)'=0'](https://img.qammunity.org/2021/formulas/mathematics/college/sjyz3pqz46pm2kg640xg07cpnlyglhdm4x.png)
![\cos(x^2+\tan y)(x^2+\tan y)'+e^(x^3\sec y)(x^3\sec y)'+2-y'=0](https://img.qammunity.org/2021/formulas/mathematics/college/9w4ce4vz0r1bzode8pji4k7vjmdbfuaahm.png)
![\cos(x^2+\tan y)(2x+\sec^2y y')+e^(x^3\sec y)(3x^2\sec y+x^3\sec y\tan y\,y')+2-y'=0](https://img.qammunity.org/2021/formulas/mathematics/college/3bwvbtzpbdgo57y3tj9gn2so8525bbapo2.png)
![\cos(x^2+\tan y)(2x+\sec^2y y')+e^(x^3\sec y)(3x^2\sec y+x^3\sec y\tan y\,y')+2-y'=0](https://img.qammunity.org/2021/formulas/mathematics/college/3bwvbtzpbdgo57y3tj9gn2so8525bbapo2.png)
![\left(\cos(x^2+\tan y)\sec^2y+x^3\sec y\tan y\,e^(x^3\sec y)-1\right)y'=-\left(2x\cos(x^2+\tan y)+3x^2\sec y\,e^(x^3\sec y)+2\right)]()
![y'=-(2x\cos(x^2+\tan y)+3x^2\sec y\,e^(x^3\sec y)+2)/(\cos(x^2+\tan y)\sec^2y+x^3\sec y\tan y\,e^(x^3\sec y)-1)](https://img.qammunity.org/2021/formulas/mathematics/college/cdbldwt62db6lu0664357ot4b83uel7n34.png)
7. Looks like
![y=x^2-e^(2x)](https://img.qammunity.org/2021/formulas/mathematics/college/hrenekcv9idcpzxam32zxq025scmptqirr.png)
Compute the second derivative:
![y'=2x-2e^(2x)](https://img.qammunity.org/2021/formulas/mathematics/college/m0py6hhyy2f2fvzmvq1svjtpdsqif0zab2.png)
![y''=2-4e^(2x)](https://img.qammunity.org/2021/formulas/mathematics/college/dtmji8xzbafrlgzgomq7z2u4vc14qj7agu.png)
Set this equal to 0 and solve for x :
![2-4e^(2x)=0](https://img.qammunity.org/2021/formulas/mathematics/college/9112vjaie1os5jyvswob3wrm6u97l5h2xg.png)
![4e^(2x)=2](https://img.qammunity.org/2021/formulas/mathematics/college/t7gi57rs2bpdedag42lvxifjifiifnt74f.png)
![e^(2x)=\frac12](https://img.qammunity.org/2021/formulas/mathematics/college/f3mkoh09p5wat4osx8vw6c71efr9e13kpt.png)
![2x=\ln\frac12=-\ln2](https://img.qammunity.org/2021/formulas/mathematics/college/io7jmboxw1as33qd2gjkn6dnakii9e4oib.png)
![x=-\frac{\ln2}2](https://img.qammunity.org/2021/formulas/mathematics/college/4k4spr99z64goavmlnyn3vfpbtaro1736d.png)